Երկրի վարկանիշի կերտման մեթոդոլոգիական հիմքերը - Փարսադանյան, Տաթևիկ
Актуальность темы является следующее: рейтинг очень важен для каждой развивающейся страны в экономическом, политическом и социальном плане. Цель статьи - проанализировать и выделить различия и сходства бренда, имиджа, рейтинга, подчеркнуть процесс установления и оценки рейтинга государства на международном уровне, несмотря на различные методологии форми-рования и развития рейтинга в литературе. Для достижения поставленной цели была решена следующая задача: процесс рейтинга — это пошаговый процесс. Перед понятием «рейтинг» необходимо пройти этапы становления идентичности, имиджа и бренда. При другой методике указанные выше понятия располагаются в системе координат и представляются с точки зрения внутреннего и внешнего восприятия. Другими словами, в процессе ранжирования важны позиции и идеи другой стороны, особенно международного сообщества, относительно вашей страны. Использовалась следующая методология: общенаучная - историко-логи-ческая и частная – системная. С их помощью были собраны и проанализированы различные методики характеристики рейтинга страны. Суть научной инновации заключается в том, что разработана концепция, позволяющая выбирать последовательность стадий рейтинга страны из разных международных рейтинговых концепций. Основным полученным результатом являются рекомендации, единая система построения рейтинга страны, а затем оценка этой системы по экономическим факторам. Полученные результаты можно применять: представить правительству страны путь повышения рейтинга страны. Указать те экономические факторы, вектор положительного изменения которых обеспечит положительный международный рейтинг. The relevance of the article lies in the fact that the formation of rating is very important for every developing country in economic, political and social terms. The purpose of the article is to analyze and distinguish the differences and similarities of the brand, image, rating, to highlight the process of establishing and evaluating the state's rating at the international level, despite the different methodologies of rating formation and development in the literature. To achieve this goal, the following objective was set: the rating process is a step-by-step process. Before the concept of "rating" one has to go through the stages of identity, image, and brand formation. With another methodology, the above-mentioned concepts are arranged on a coordinate system and presented from the point of view of internal and external perception. In other words, the positions and ideas of the other party, especially the international community, regarding your country are important in the ranting process. The following methodology was used: general scientific - historical-logical and private - collection. Through them, different methodologies for characterizing the country's rating were collected and analyzed. The essence of the scientific innovation is that a concept has been developed that allows choosing the sequence of the country's rating stages from different international rating concepts. An approach to rating assessment was derived in accordance with economic factors, on the basis of which reforms were developed to improve the rating. The main obtained results are the recommendations, a unified system for the formation of country's rating, and later the evaluation of that system according to economic factors. It is possible to apply the obtained results: to show the way of increasing the country's rating the government. Point out the economic factors whose vector of positive change will ensure a positive international rating.
Keywords: Տնտեսություն